Chronic Disease Self-Management Education (CDSME) Program Delivery and Attendance among Urban-Dwelling African Americans - Mingo, Chivon A.; Smith, Matthew Lee; Ahn, SangNam; Jiang, Luohua; Cho, Jinmyoung; Towne, Samuel D.; Ory, Marcia G. (Frontiers in Public Health, 2015)
.